Boundary layer flow over a moving surface in a nanofluid beneath a uniform free stream - Mohd Rohni, Azizah; Ahmad, Syakila; Pop, Ioan (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this paper is to theoretically investigate the steady two‐dimensional boundary‐layer flow past a moving semi‐infinite flat plate in a water‐based nanofluid containing three different types of nanoparticles: copper (cuprum) Cu, alumina (aluminium oxide) Al2O3, and titania (titanium dioxide) TiO2.The effects of moving parameter λ as well as solid volume fraction parameter φ on the flow and heat transfer characteristics are studied.Taking into account the rising demands of modern technology, including chemical production, power stations and microelectronics, there is a need to develop new types of fluids that will be more effective in terms of heat exchange performance.Design/methodology/approach – A similarity transformation is used to reduce the governing partial differential equations to a set of nonlinear ordinary differential equations which are then solved numerically using Keller‐box method.Findings– There is a region of unique solutions for λ>0, however, multiple (dual) solutions exist for λc<λ≤0 and no solutions for λ<λc<0. A reverse flow is formed when λ<0.Research limitations/implications– The solutions can be obtained up to a certain value of the moving parameter (critical value or turning point). The boundary layer separates from the plate beyond the turning point hence it is not possible to get the solution based on the boundary‐layer approximations after this point. To obtain further solutions, the full Navier‐Stokes equations have to be solved.Originality/value– The present results are original and new for the boundary‐layer flow and heat transfer of a moving flat plate in a nanofluid. Therefore, this study would be important for the scientists and engineers in order to become familiar with the flow behaviour and properties of such nanofluids, and the way to predict the properties of this flow for the process equipments.